International development cooperation and political risks for transnational business: Linking research topics - V. I. Bartenev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
International development cooperation and political risks for transnational business are two topics which have always drawn attention from specialists in international political economy. Each of these topics is studied by a dedicated subdiscipline with a specific terminology, strong analytical centers and influential peer-reviewed journals. Despite political risks had initially been associated with developing countries (and transition economies — after the Cold War), two distinctive research clusters have developed separately from one another — quite inexplicably. Drawing on the idea of immanent proximity of international development studies and political risk analysis, this paper develops the logic of blending their research agendas.The first two sections formulate key presumptions meant to justify the conjugation of two topics. The first presumption is an acknowledgement of an engrained commercial motivation in any modality of development cooperation and the latter’s ability to serve as a tool to promote foreign economic interests. The second presumption emphasizes the existence of an indissoluble link between political risks for business with socio-economic and political development disbalances within and between countries. The final section identifies concrete dimensions of conjugation of two research agendas, such as: 1) conducting political risk assessments in the course of programming and implementing development projects; 2) examining the impact of political risk manifestations on provider countries’ ability to mobilize financial resources for international development; studying the practices of using different development cooperation tools to mitigate political risks for foreign economic activity — both through a direct and deliberate reduction of risk perceived by business and through an indirect impact on the environment where political risks are formed; 4) exploring the logic of emergence of new risk factors (of various types) in the course of implementing development cooperation policies. The conclusion argues for focusing on the reverse impact of new trends in international development cooperation on the parameters of political risks for international business from the Western and non-Western countries amidst the global turbulence, using all available sources of statistical data — conventional and unconventional. It also draws a step-by-step research plan and assesses the theoretical and policy relevance of obtaining anticipated results.